Nosocomial Pneumonia: An Updated Review for Healthcare Professionals - Alessaimi, Sana Mohaimeed; Alanzi, Ahlam Masnad; Alonazi, Mariam Khalaf; Motaen , Najwa Mohammed Nasser; Alanazi , Saad Bandar; Aljubaili, Abduladeem Radi; Alsharari, Bader Falah Duwayshir; Alsharari, Najeh Falah Duwayshir; Alsharari, Saif Dulayman Salamah; Dagrriry , Fatimah Ali Ahmed; Qaisi, Amal Abutalip Jurdi; Aljohani , Hanadi Mohammed Ali; et al. (Journal of Ecohumanism, 2024)
Background: Nosocomial pneumonia, including hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP), is a leading cause of morbidity and mortality in healthcare settings. HAP is defined as pneumonia occurring 48 hours or more after hospital admission, while VAP develops 48 to 72 hours after endotracheal intubation. These infections are associated with prolonged hospital stays, increased healthcare costs, and high mortality rates, particularly among critically ill patients. The rise of multidrug-resistant (MDR) pathogens further complicates treatment, underscoring the need for effective prevention, accurate diagnosis, and evidence-based management strategies. Aim: This review aims to provide healthcare professionals with an updated understanding of the etiology, risk factors, epidemiology, clinical presentation, diagnostic approaches, treatment strategies, and preventive measures for HAP and VAP. It emphasizes the importance of a multidisciplinary approach to improve patient outcomes and reduce the burden of these infections. Methods: The review synthesizes current guidelines, clinical studies, and expert recommendations on HAP and VAP. It examines the pathogenesis, common pathogens, and risk factors for MDR infections. Diagnostic methods, including clinical evaluation, microbiologic testing, and advanced molecular diagnostics, are discussed. Treatment strategies, including empiric and targeted antibiotic therapy, are outlined, along with recommendations for antimicrobial stewardship. The role of an interprofessional team in managing HAP and VAP is highlighted. Results: HAP and VAP are primarily caused by gram-negative bacilli (e.g., Pseudomonas aeruginosa, Escherichia coli) and gram-positive cocci (e.g., Staphylococcus aureus, including MRSA). Risk factors for MDR pathogens include recent antibiotic use, prolonged hospitalization, and severe illness. Diagnosis relies on clinical criteria, imaging, and microbiologic testing, with molecular diagnostics offering rapid pathogen identification. Empiric therapy should cover MRSA and Pseudomonas aeruginosa, with de-escalation based on culture results. A 7-day antibiotic course is generally effective, though longer durations may be needed for severe cases. Preventive measures, such as hand hygiene, ventilator care bundles, and antimicrobial stewardship, are critical. Conclusion: HAP and VAP remain significant challenges in healthcare, with high morbidity and mortality rates. Effective management requires a multidisciplinary approach, early diagnosis, appropriate antibiotic use, and robust infection control measures. Ongoing research and adherence to evidence-based guidelines are essential to improving outcomes and reducing the impact of these infections.